Caputo fractional differential equations for low–risk individuals of the tuberculosis transmission disease - Nik Long, Nik Mohd Asri; Nawaz, Rashid; Shohaimi, Shamarina (Universiti Putra Malaysia, 2024)
In this article, the Caputo fractional order model with low risk individuals of the tuberculosis is proposed. We investigate a qualitative analysis of the epidemic model via positivity, existence and uniqueness, stability and threshold quantity. Conducting a sensitivity analysis and examining the dynamics of threshold parameters enable the assessment of the efficacy of preventive measures, prediction of future outbreaks, and the formulation of potential strategies for disease control. Numerical computations are executed using the Laplace Adomian decomposition method. The findings imply that the increment of low risk individuals can mitigate the prevalence and impact of tuberculosis on the human population in the respective region.